EP863 Ovarian primitive lymphoma: experience of department of medical oncology algiers, algeria. (1st November 2019) - Hadjarab, F; Chekman, CE; Taibi, A; Bouzid, K
Abstract : Introduction/Background: The non-Hodgkin lymphomas primary ovarian malignancies are rare (1.5% of ovarian cancers, 0.5% of NHL) lymphoid tissue that can develop in extranodal sites. whose histogenesis is controversial. Indeed, some authors consider it as an initial manifestation of a generalized lymphomatous disease. The prognosis depends on several factors, including clinical stage, histological type and phenotype, Ovarian primary location is exceptional. - Criteria for ovarian lymphoma primitive defined by FOX and LANGLEY: To retain the diagnosis of primary lymphoma of the ovary; Four criteria are required: Location ovary at diagnosis. Lack of simultaneous extension to another body. Lack of leukemia. Monitoring of months to eliminate an extra recurrent genital. Methodology: We report in this post about 05 comments a retrospective study of 05 cases of ovarian lymphoma supported the medical oncology unit at CPMC, observed 619 cases of ovarian malignancies. This represents 0.80% operated and treated with chemotherapy (CHOP Protocol 4, 1 RCHOP). Treatment: Surgery followed by chemotherapy. - Rests primarily on the standard R-CHOP chemotherapy: - Rituximab (anti CD20 mAb) - Cyclophosphamide - Doxorubicin - Vincristine - Prednisolone. Results: The therapeutic results were: 03 patients in complete remission; with a decline of 32, 24, and 18 months. Treatment failure in a patient who died after falling 14 months a scheduled these courses of chemotherapy but has not presented patient died as a result of kidney failure two months after surgery. Conclusion: Tumeurs Rare. – Young woman under 50. The clinical, biology, imaging are nonspecific making it difficult. Preoperative diagnosis. Treatment is primarily based on the medical chemotherapy. Key role of extemporaneous analysis before an unusual tumor young woman to avoid bilateral castration and maintain the possibility of pregnancy after chemotherapy. FACTORS are ill PROGNOSIS: Medulla injury and neuro-brain - HIV seropositivity - Translocation 14.18 - Failed chemotherapy - but frequently. Disclosure: No conflict of interest.